Psychological Capital of MIS Development Teams, System Effectiveness, and Social Innovation: A Systematic Literature Review - Tang, Yuan; Shao, Yun-Fei (Frontiers in Psychology, 2019)
Inter-organizational information systems are critical in the modern business world, as a large portion of economic activities are done through inter-organizational collaborations. One such important collaboration is social innovation/entrepreneurship, which involves multiple parties from diverse areas cooperating in major tasks. Against such a backdrop, exploring beneficial factors for organizational members to actively develop and/or make good use of a management information system (MIS) for collaborative performance has become a vital research question. This conceptual paper argues that positive psychology is critical to encourage members to volunteer to construct an MIS that facilitates social innovation effectiveness. Specifically, we discuss the four dimensions of psychological capital (i.e., hope, optimism, self-efficacy, and resilience) on effective inter-organizational MIS attributes (e.g., connectivity), and on the consequences of social innovation. At the core of this discussion, we believe that a positive psychological foundation is a driver for staff effort to contribute to a better MIS, which could benefit social innovation success. This research contributes by offering inspiration for future studies to link the micro- and macro-level aspects of social innovation and entrepreneurship phenomena.